Screening of periodontal disease related Bacteria in Iraqi patients and their relationship with salivary TLR2 and IL-6 level - Hussein, Fatima; Abdul Sattar, Moroj (Iraqi Journal of Science, 2023)
The oral cavity has the second major and most diverse microflora after the gut. Since it is the starting point of digestion; the oral microbiota is essential for maintaining oral and systemic health. Thus, this study aimed to find the bacterial isolates which act as a causative agent of periodontal diseases in Iraqi patients and their relation with some immune oral parameters. Saliva specimens and oral swabs of 91 patients (51) and control individuals (40) were collected in this study. The specimens of patients were collected from Al-Amirya and Almaamon Specialized Dental Centers in Baghdad for a period from November/2021 to February/2022. The microbiological results revealed, that the most prevalent bacterial isolates were related to the genus, which was descending graduated into Staphylococcus spp.74.5%> Enterobacteriaceae spp.62.7% > Streptococcus spp. 13.7% and Acinetobacter spp.13.7% > Neisseria spp.9.8% > Bacillus spp.5.8% > Corynebacterium spp. 3.9% and Pseudomonas spp.3.9%, and in the same context, the acidic pH of the patient's or control's mouths is more conducive for bacterial development than other pH items. As well by using the ELISA technique, the soluble form of TLR2 7.384 ± 4.031 ng/ml elucidated a significant increase in patients than the control group 5.313 ± 3.106 ng/ml, while interleukin 6 shows a strange increase in both patients and the control group saliva 50161 ± 63869, 52087 ± 62756 ng/ l respectively.